2017
DOI: 10.3389/fpls.2017.00602
|View full text |Cite
|
Sign up to set email alerts
|

Fine Root Abundance and Dynamics of Stone Pine (Pinus cembra) at the Alpine Treeline Is Not Impaired by Self-shading

Abstract: Low temperatures are crucial for the formation of the alpine treeline worldwide. Since soil temperature in the shade of tree canopies is lower than in open sites, it was assumed that self-shading may impair the trees’ root growth performance. While experiments with tree saplings demonstrate root growth impairment at soil temperatures below 5–7°C, field studies exploring the soil temperature – root growth relationship at the treeline are missing. We recorded soil temperature and fine root abundance and dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 63 publications
(105 reference statements)
1
16
0
Order By: Relevance
“…We estimated annual fine root production with the ingrowth core technique (Majdi, 1996), which has been used in studies worldwide (e.g. Chen et al, 2004;Hendricks et al, 2006;Handa et al, 2008;Adamek et al, 2011;Kubisch et al, 2017). Measurements in temperate forests have shown that this method tends to provide rather conservative values of fine root production compared with other approaches such as sequential coring and minirhizotrons (e.g.…”
Section: Fine Root Production and Turnovermentioning
confidence: 99%
See 1 more Smart Citation
“…We estimated annual fine root production with the ingrowth core technique (Majdi, 1996), which has been used in studies worldwide (e.g. Chen et al, 2004;Hendricks et al, 2006;Handa et al, 2008;Adamek et al, 2011;Kubisch et al, 2017). Measurements in temperate forests have shown that this method tends to provide rather conservative values of fine root production compared with other approaches such as sequential coring and minirhizotrons (e.g.…”
Section: Fine Root Production and Turnovermentioning
confidence: 99%
“…We restored the original soil horizon sequence and soil bulk density as good as possible. No mesh was used to avoid barriers for root growth and to retain natural conditions (Hertel et al, 2013;Kubisch et al, 2017) without impeding the access of the soil dwelling fauna. The locations were precisely marked with three plastic sticks to enable Given are means with SE (in brackets).…”
Section: Fine Root Production and Turnovermentioning
confidence: 99%
“…The increasing crown cover will reduce growing season soil temperature in the rooting zone and may thus impede root growth. Whatsoever, field studies on the response of Swiss stone pines to low soil temperatures as a result of self-shading have provided evidence that fine roots abundance and dynamics at the treeline is not affected by self-shading [396]. whether seed-based regeneration within the treeline ecotone and in the lower alpine zone will be successful or fail.…”
Section: Feedbacks Of Increasing Tree Populationmentioning
confidence: 99%
“…The increasing crown cover will reduce growing season soil temperature in the rooting zone and may thus impede root growth. Whatsoever, field studies on the response of Swiss stone pines to low soil temperatures as a result of self-shading have provided evidence that fine roots abundance and dynamics at the treeline is not affected by selfshading [396]. It has even been argued that densely grouped trees themselves would reduce their possible lifetime through shading the ground [86], whereas, sunlit patches between wide-spaced trees and tree groups usually exhibit higher daytime soil temperatures during the growing season (e.g., [20,22,23,27,131,147,397-401]), that might facilitate tree establishment.…”
Section: Feedbacks Of Increasing Tree Populationmentioning
confidence: 99%
“…Below-ground plant community responses to resource supply or constraints are rarely studied but are providing important clues as to how communities respond to changes in land use and climate (Prieto et al, 2015(Prieto et al, , 2016. Heterogeneous forest ecosystems should be investigated in a similar holistic manner in order to predict and model forest responses to climate variability (Kitajima et al, 2010;Kubisch et al, 2017). The structure of a forest community will also affect local climatic conditions, especially with regard to open and closed canopies that alter the biophysical environment both above-and below-ground.…”
Section: Introductionmentioning
confidence: 99%